Implementasi Aplikasi Game Edukasi Multimedia Interaktif Untuk Memperkenalkan Alat Musik Tradisional Jawa Barat Berbasis Android - Nashrulloh, Muhammad Rikza; Patria, Dhika Muhamad (Jurnal Algoritma, 2025)
The advancement of information and communication technology (ICT) has had a significant impact on various sectors, including education. One of the latest innovations in this field is interactive multimedia-based educational games, which offer more engaging learning methods. In Garut Regency, West Java, the introduction of traditional musical instruments faces challenges due to limited access and teaching methods that are less appealing to elementary school students. To address this issue, this study proposes the development of an Android-based educational game application aimed at introducing traditional musical instruments of West Java, such as angklung, suling, calung, kecapi, rebab, jentreng, karinding, arumba, jengglong, and celempung. The application is developed using the Multimedia Development Life Cycle (MDLC) methodology. It provides features to learn the shape and how to play each instrument, along with quizzes to assess students’ understanding. Previous studies have shown that educational games can increase interest and understanding of traditional culture through interactive approaches. This application is expected to be an effective solution to preserve and introduce traditional musical instruments to elementary school students, as well as to foster a sense of pride in their local culture. This research aims to contribute to the preservation of local culture by utilizing interactive multimedia technology and can serve as a reference for the development of similar educational applications in the future.